Electromagnetic fields in the vicinity of DECT cordless telephones and mobile phones - Paweł Mamrot; Magda Mariańska; Halina Aniołczyk; Piotr Politański (Nofer Institute of Occupational Medicine, 2015)
Background: Mobile telephones belong to the most frequently used personal devices. In their surroundings they produce the electromagnetic field (EMF), in which exposure range there are not only users but also nearby bystanders. The aim of the investigations and EMF measurements in the vicinity of phones was to identify the electric field levels with regard to various working modes. Material and methods: Twelve sets of DECT (digital enhanced cordless telecommunications) cordless phones (12 base units and 15 handsets), 21 mobile telephones produced by different manufactures, and 16 smartphones in various applications, (including multimedia) in the conditions of daily use in living rooms were measured. Measurements were taken using the point method in predetermined distances of 0.05-1 m from the devices without the presence of users. Results: In the vicinity of DECT cordless phone handsets, electric field strength ranged from 0.26 to 2.30 V/m in the distance of 0.05 m - 0.18-0.26 V/m (1 m). In surroundings of DECT cordless telephones base units the values of EMF were from 1.78-5.44 V/m (0.05 m) to 0.19- 0.41 V/m (1 m). In the vicinity of mobile phones working in GSM mode with voice transmission, the electric field strength ranged from 2.34-9.14 V/m (0.05 m) to 0.18-0.47 V/m (1 m) while in the vicinity of mobile phones working in WCDMA (Wideband Code Division Multiple Access) mode the electric field strength ranged from 0.22-1.83 V/m (0.05 m) to 0.18-0.20 V/m (1 m). Conclusions: The mean values of the electric field strength for each group of devices, mobile phones and DECT wireless phones sets do not exceed the reference value of 7 V/m, adopted as the limit for general public exposure. Med Pr 2015;66(6):803-814